Liberalization and Structural Change: Evidence from Nepalese Manufacturing - Kishor Sharma (Yale University, Economic Growth Center, 2000)
The consequences of liberalization on structural changes are examined using data from manufacturing industry in Nepal which is classified as a least developed country. This is important because doubts that liberalization may not solve the problems of low-income developing countries remain strong due mainly to low supply elasticities and the early stage of industrialization. Results suggest some structural changes in manufacturing output and trade orientation. However, no significant improvements were recorded in the overall productivity growth and spatial distribution of manufacturing which appear to be due mainly to the lack of basic infrastructure and the shortage of skilled manpower. Thus, appropriate investment policies, which channel resources to improve human capital and infrastructure, appear to be essential if the potential benefits of liberalization are to be fully achieved.
Keywords: E13; F13; F14; F43; 330; liberalization; import penetration; export intensity; total factor productivity growth; Nepal; Handelsliberalisierung; Produktivität; Strukturwandel; Schätzung; Nepal